2022
DOI: 10.1002/jib.682
|View full text |Cite
|
Sign up to set email alerts
|

Towards lager beer aroma improvement via selective amino acid release by proteases during mashing

Abstract: Higher alcohols and esters are key compounds from fermentation that help define the character of beer. Higher alcohols are mainly produced by yeast via the Ehrlich amino acid degradation pathway of especially leucine, isoleucine, valine, and phenylalanine. Augmenting the concentration of these amino acids can enhance the output of the Ehrlich pathway. Unlike previous studies, the work reported here explores the possibility of combining endo-and exo-proteases to selectively release these amino acids to potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, based on the previous investigations it has been reported that endo-proteases plays predominant role in release of amino acid during malting and mashing. Recently, Lin et al (2022) applied combinations of endo-and exo-proteases in mashing to enrich wort amino acids and reported the major influence of endo-protease, which was confirmed by the amino acid enrichment due to addition of the endo-protease alone in mash. can reduce the detectable levels of protein in mashes and induce the generation of free amino nitrogen, demonstrating that there is no inherent factor that prohibits the functioning of this type of enzyme in mashes.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, based on the previous investigations it has been reported that endo-proteases plays predominant role in release of amino acid during malting and mashing. Recently, Lin et al (2022) applied combinations of endo-and exo-proteases in mashing to enrich wort amino acids and reported the major influence of endo-protease, which was confirmed by the amino acid enrichment due to addition of the endo-protease alone in mash. can reduce the detectable levels of protein in mashes and induce the generation of free amino nitrogen, demonstrating that there is no inherent factor that prohibits the functioning of this type of enzyme in mashes.…”
Section: Discussionmentioning
confidence: 90%
“…However, based on the previous investigations it has been reported that endo‐proteases plays predominant role in release of amino acid during malting and mashing. Recently, Lin et al (2022) applied combinations of endo‐ and exo‐proteases in mashing to enrich wort amino acids and reported the major influence of endo‐protease, which was confirmed by the amino acid enrichment due to addition of the endo‐protease alone in mash. Aldred et al.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This could contribute to the change in the quality of bitterness when brewing with unmalted barley (Yorke et al 2021). The importance of utilising proteolytic enzymes to increase free amino nitrogen for the formation of flavour-active volatile compounds is well understood (Hill and Stewart 2019;Lei et al 2013a, b;Lin et al 2022). However, these results show the importance of proteolytic enzymes and the hydrolysis of proteins in the formation of taste inducing peptides in the beer.…”
Section: Peptidesmentioning
confidence: 99%